Transnational radicalism and the connected lives of Tom Mann and Robert Samuel Ross - Kirk, Neville, 1947- (Liverpool : Liverpool University Press, 2017)
A pioneering study of the neglected transnational activities and influences of two important, connected socialists, British-born Tom Mann (1856-1941) and Australian-born Robert Samuel 'Bob' Ross (1873-1931).
Cover -- Contents -- Acknowledgements -- Introduction -- II The Transnational Context -- Introduction -- Issues and Debates -- The Transnational World of Mann and Ross -- II Socialism -- Introduction -- What Kind of Socialism? -- Unfolding Differences, Enduring Similarities -- III Womanhood, Whiteness and War -- Introduction -- â#x80;#x98;True Womanhoodâ#x80;#x99; -- Race and Whiteness -- World War I and its Aftermath -- Conclusion -- Bibliography
Includes bibliographical references (pages 253-276) and index.
JSTOR
Keywords: Mann, Tom, -- 1856-1941.; Ross, R. S; Mann, Tom, -- 1856-1941; Socialists -- Biography; Socialism -- History -- 20th century; HISTORY -- General; Socialism; Socialists; 1900-1999; Biographies; History